(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the actual issues of teaching the subject of human and social geography. The state of teaching geography in foreign countries. The mechanism of development of skills in the subject of “economic and social geography” in students. The application of the technology” cheerful map " is illuminated.